Manual development and efficacy of Mindful Living Group activities to promote trauma healing during the COVID-19 pandemic in China - Niu, Ya-Nan; Long, Di (Frontiers in Public Health, 2023)
Introduction Disasters can be traumatic with a profound and lasting impact on individuals. During the COVID-19 pandemic, our team developed the Mindful Living Group (MLG) activities manual based on Eastern body-mind wisdom and Western trauma healing theory to provide psychological assistance for trauma healing. Methods In this study, we introduce a framework developed for the 10-session MLG activities manual, which consists of three core modules. Thirty-one participants living all over the country who had experienced traumatic stress resulting from the COVID-19 pandemic received the MLG intervention. This single-arm intervention study offered psychological assistance during the pandemic. The MLG intervention included 10 weekly 2-h sessions held online. Participants completed the initial interview, pre-test, post-test, and 1-month follow-up interviews. The effectiveness of the MLG activities manual was evaluated using psychological measures, including Self-Rating Depression Scale, Self-Rating Anxiety Scale, Mindful Attention Awareness Scale, Post-traumatic Growth Inventory, General Self-Efficacy Scale, and the Perceived Social Support Scale. Results Compared with the pretest level, the post-test levels of depression (F = 42.78, p < 0.001, η2 = 0.59) and anxiety (F = 23.40, p < 0.001, η2 = 0.44) were significantly lower; and mindfulness (F = 12.98, p =0.001, η2 =0.30), posttraumatic growth (F = 27.06, p < 0.001, η2 = 0.48), general self-efficacy (F = 13.20, p = 0.001, η2 = 0.31), and perceived social support (F = 16.27, p < 0.001, η2 = 0.35) were significantly higher (ANOVA). Further correlation analysis revealed a significant negative relationship of mindfulness with both depression (r = −0.43, p = 0.015) and anxiety (r = −0.35, p = 0.053), and significant positive relationships of mindfulness with posttraumatic growth (r = 0.40, p = 0.025), general self-efficacy (r = 0.52, p = 0.003), and perceived social support (r = 0.40, p = 0.024). Discussion These preliminary findings showed the effectiveness of MLG activities for trauma healing. The mechanisms underlying mindfulness promoting trauma healing are discussed based on both Eastern body-mind wisdom and Western theories of trauma healing. Clinical trial registration Identifier, ChiCTR2000034164.